Introduction to international disaster management - Coppola, Damon P (Elsevier/Butterworth-Hein, 2015)
This comprehensive overview of global emergency management provides practitioners and students alike with an understanding of the disaster management profession by using a global perspective, including the different sources of risk and vulnerability, the systems that exist to manage hazard risk, and the many stakeholders involved. This update examines the impact of recent large-scale and catastrophic disaster events on countries and communities, as well as their influence on disaster risk reduction efforts worldwide. It expands coverage of small-island developing states and explores the achievements of the United Nations Hyogo Framework for Action (2005-2015) and the priorities for action in the Post-2015 Framework for Disaster Risk Reduction currently under development.